Path Dependence on New Roads: Institutional Development of Quality Registers - Örnerheim, Mattias; Wihlborg, Elin (Scandinavian Journal of Public Administration, 2014)
When explaining social development and changes in public administration, institutional change is a typical focus. Institutional analysis can combine the analyses of changes on the basis of formal legal and informal arrangements; it commonly shows that institutions lead to inertia where changes over time are concerned. Political aims are a guide to how organizations are designed and governed. When goals and earlier decisions clearly guide change, path dependence is a fundamental concept when explaining change. However, this analysis shows how and when quality registers appeared as an answer to changes in institutional arrangements in Swedish public healthcare. Through three phases, cumulative processes have been visible and the processes have been followed by an improved and increased usage of quality registers and other quality systems. This analysis shows that institutional development can be path-dependent in relation to methods and means. Despite changing goals over time, quality registers as a policy tool have been path-dependent and stayed firm. Thus, it is important to see also organisational methods as a development path that can be used to implement even new policy aims.